Fatigue behavior of low-temperature hot isostatic pressed electron beam powder bed fusion manufactured Ti-6Al-4 V - Pandian K; Neikter M; Bahbou F; Ganvir A; Hansson T; Pederson R (Elsevier Science, 2025)
Ti-6Al-4 V finds application in the fan and compressor modules of gas turbine engines due to its high specific strength. Ti-6Al-4 V components manufactured using one of the additive manufacturing (AM) techniques, the electron beam powder bed fusion (PBF-EB) process, has been an active area of research in the past decade. The fatigue life of such PBF-EB built Ti-6Al-4 V components is improved by hot isostatic pressing (HIP) treatment typically performed at about 920 C. The HIP treatment at 920 C results in coarsening of & alpha; laths and reduced static strength and therefore a low-temperature HIP treatment is performed at about 800 C to limit the impact on static mechanical properties. In the present work, the low cycle fatigue and fatigue crack growth behavior of such a modified HIP (low-temperature HIP) treated material is assessed and compared with the respective data for the standard HIP-treated material. The modified HIP-treated material has fatigue performance comparable to the standard HIP-treated material. This work suggests that the modified HIP treatment improves the static mechanical properties without significantly impacting the fatigue performance. Also, fatigue life predictions were made from the measured defect size at the crack initiation site using a linear elastic fracture mechanics tool. The life predictions show good agreement with the experimental values for defects greater than the intrinsic crack length, where life is well predicted by large-crack growth methodology.